2016
DOI: 10.3844/ajavsp.2016.41.46
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inclusion of <i>Albizia saman</i> Pods in the Diet on the Performances of Dairy Cows

Abstract: Ruminants can achieve high productivity when the diet includes concentrates; however these are often expensive due to competition with humans and mono-gastric animals. This experiment was conducted to determine the effect of partial inclusion of Albizia saman pods (ASP) in a Commercial Concentrate (CC) on the performances of dairy cows. Twelve cross-bred Holstein Friesian cows (472±13 kg) in the 12th week of lactation were randomly allocated into four treatment groups with three replicates accoding to the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The dry matter, proximate, metabolic energy (ME) and selected anti-nutrients compositions of sun-dried ripe rain tree pods are presented in Table 2. Dried pods had a dry matter (DM) content of 95.10%, a value similar to that reported by Raja et al (2017) but higher than values ranging between 81.73 and 85.50 reported by Hosamani et al (2005), Esquivel-Mimenza et al (2014 and Aung et al (2016). The high level of DM obtained could be explained by the intensity of drying, which was done to allow for the ease of milling, handling and storage of the pods.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The dry matter, proximate, metabolic energy (ME) and selected anti-nutrients compositions of sun-dried ripe rain tree pods are presented in Table 2. Dried pods had a dry matter (DM) content of 95.10%, a value similar to that reported by Raja et al (2017) but higher than values ranging between 81.73 and 85.50 reported by Hosamani et al (2005), Esquivel-Mimenza et al (2014 and Aung et al (2016). The high level of DM obtained could be explained by the intensity of drying, which was done to allow for the ease of milling, handling and storage of the pods.…”
Section: Resultssupporting
confidence: 74%
“…Rain trees (Albizia saman) are grown along roadsides and gardens as avenue trees, in parks for shade and ornamentals, and are also planted as pasture trees (Flores, 2002;Hosamani et al, 2005;Aung et al, 2016). They are fast-growing, easy to cultivate (Idowu et al, 2006) and are cultivated and/or naturalized throughout the tropics (Durr, 2001;Staples and Elevitch, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Gao and Oba [ 16 ] stated that the feed intake of the dairy cow was enhanced by a high NFC and TDN diet. Aung et al [ 17 ] reported that dietary inclusion of Albizia saman pods improved the DMI and nutrient intake of lactating dairy cows because of its higher NFC and energy density.…”
Section: Resultsmentioning
confidence: 99%
“…Milk yield and compositions were not influenced by MPM supplementation, which agreed with Kanpakdee and Wanapat (2008) with lower dietary inclusions of mangosteen peel (158 g CT/kg and 98 g SP/kg) at 200 g/head/day. Aung, Kyawt, Htun, Mu, and Aung (2016) who reported that inclusion of Albizia saman pods (19 g tannins/ kg) at 5%-15% in the diets did not affect milk production and milk compositions in dairy cows. In contrast, Anantasook et al (2015) reported that supplementation of Samanea saman (88 g CT/kg and 141 g SP/kg) at 60 g/kg increased milk yield and milk protein in dairy cows.…”
Section: Milk Production and Compositionsmentioning
confidence: 99%